A line always passing the point

Geometry Level 4

l l is a line passing through the focus F F of the parabola C : y 2 = 2 p x ( p > 0 ) C:y^2=2px \ (p>0) and intersects with the parabola at point A A and B B .

Let point D D be the symmetry point about the x-axis of point A A , line B D BD (if exists) will always pass through the point ( λ p , 0 ) (\lambda p,0) . Find the value of λ \lambda .


The answer is -0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Nick Kent
Aug 19, 2019

Since C : y 2 = 2 p x C: { y }^{ 2 }=2px , F = ( p 2 , 0 ) F=\left( \frac { p }{ 2 } ,0 \right) . Then let l : k y = x p 2 l:k\cdot y=x-\frac { p }{ 2 } .

Let's find the intersections, l × C : l\times C:

( x p 2 ) 2 = 2 k 2 p x x 2 p x + p 2 4 = 2 k 2 p x x 2 ( 1 + 2 k 2 ) p x + p 2 4 = 0 { \left( x-\frac { p }{ 2 } \right) }^{ 2 }=2{ k }^{ 2 }\cdot p\cdot x\\ { x }^{ 2 }-p\cdot x+\frac { { p }^{ 2 } }{ 4 } =2{ k }^{ 2 }\cdot p\cdot x\\ { x }^{ 2 }-\left( 1+2{ k }^{ 2 } \right) \cdot p\cdot x+\frac { { p }^{ 2 } }{ 4 } =0

x 1 , 2 = ( 1 + 2 k 2 ) p 2 ± ( 1 + 2 k 2 ) 2 p 2 4 p 2 4 x 1 , 2 = ( 1 + 2 k 2 ) p 2 ± ( 1 + 2 k 2 ) 2 1 p 2 x 1 , 2 = ( 1 + 2 k 2 ) p 2 ± 4 k 2 + 4 k 4 p 2 x 1 , 2 = ( 1 + 2 k 2 ± 2 k 1 + k 2 ) p 2 { x }_{ 1,2 }=\left( 1+2{ k }^{ 2 } \right) \cdot \frac { p }{ 2 } \pm \sqrt { \frac { { \left( 1+2{ k }^{ 2 } \right) }^{ 2 }\cdot { p }^{ 2 } }{ 4 } -\frac { { p }^{ 2 } }{ 4 } } \\ { x }_{ 1,2 }=\left( 1+2{ k }^{ 2 } \right) \cdot \frac { p }{ 2 } \pm \sqrt { { \left( 1+2{ k }^{ 2 } \right) }^{ 2 }-1 } \cdot \frac { p }{ 2 } \\ { x }_{ 1,2 }=\left( 1+2{ k }^{ 2 } \right) \cdot \frac { p }{ 2 } \pm \sqrt { 4{ k }^{ 2 }+4{ k }^{ 4 } } \cdot \frac { p }{ 2 } \\ { x }_{ 1,2 }=\left( 1+2{ k }^{ 2 }\pm 2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { p }{ 2 }

Knowing x 1 , 2 { x }_{ 1,2 } , we can derive y 1 , 2 { y }_{ 1,2 } :

y = x p 2 k y 1 , 2 = ( k ± 1 + k 2 ) p y=\frac { x-\frac { p }{ 2 } }{ k } \\ { y }_{ 1,2 }=\left( k\pm \sqrt { 1+{ k }^{ 2 } } \right) \cdot p

Thus we got points A A and B B :

A = ( ( 1 + 2 k 2 + 2 k 1 + k 2 ) p 2 , ( k + 1 + k 2 ) p ) B = ( ( 1 + 2 k 2 2 k 1 + k 2 ) p 2 , ( k 1 + k 2 ) p ) A=\left( \left( 1+2{ k }^{ 2 }+2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { p }{ 2 } ,\left( k+\sqrt { 1+{ k }^{ 2 } } \right) \cdot p \right) \\ B=\left( \left( 1+2{ k }^{ 2 }-2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { p }{ 2 } ,\left( k-\sqrt { 1+{ k }^{ 2 } } \right) \cdot p \right)

Since point D D is the symmetry point about the x-axis of point A A :

D = ( ( 1 + 2 k 2 + 2 k 1 + k 2 ) p 2 , ( k 1 + k 2 ) p ) D=\left( \left( 1+2{ k }^{ 2 }+2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { p }{ 2 } ,\left( -k-\sqrt { 1+{ k }^{ 2 } } \right) \cdot p \right)

Now we can consider the line B D BD :

Δ x = x D x B = 2 k 1 + k 2 p Δ y = 2 k p \Delta x={ x }_{ D }-{ x }_{ B }=2k\sqrt { 1+{ k }^{ 2 } } \cdot p\\ \Delta y=-2k\cdot p

Then, B D : x x B Δ x = y y B Δ y BD:\frac { x-{ x }_{ B } }{ \Delta x } =\frac { y-{ y }_{ B } }{ \Delta y }

Let x = λ p , y = 0 x=\lambda \cdot p,y=0 :

λ p ( 1 + 2 k 2 2 k 1 + k 2 ) p 2 2 k 1 + k 2 p = 0 ( k 1 + k 2 ) p 2 k p λ ( 1 + 2 k 2 2 k 1 + k 2 ) 1 2 2 k 1 + k 2 = k 1 + k 2 2 k λ ( 1 + 2 k 2 2 k 1 + k 2 ) 1 2 1 + k 2 = k 1 + k 2 λ ( 1 + 2 k 2 2 k 1 + k 2 ) 1 2 = k 1 + k 2 1 k 2 λ 1 2 k 2 + k 1 + k 2 = k 1 + k 2 1 k 2 λ = 1 2 \frac { \lambda \cdot p-\left( 1+2{ k }^{ 2 }-2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { p }{ 2 } }{ 2k\sqrt { 1+{ k }^{ 2 } } \cdot p } =\frac { 0-\left( k-\sqrt { 1+{ k }^{ 2 } } \right) \cdot p }{ -2k\cdot p } \\ \frac { \lambda -\left( 1+2{ k }^{ 2 }-2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { 1 }{ 2 } }{ 2k\sqrt { 1+{ k }^{ 2 } } } =\frac { k-\sqrt { 1+{ k }^{ 2 } } }{ 2k } \\ \frac { \lambda -\left( 1+2{ k }^{ 2 }-2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { 1 }{ 2 } }{ \sqrt { 1+{ k }^{ 2 } } } =k-\sqrt { 1+{ k }^{ 2 } } \\ \lambda -\left( 1+2{ k }^{ 2 }-2k\sqrt { 1+{ k }^{ 2 } } \right) \cdot \frac { 1 }{ 2 } =k\sqrt { 1+{ k }^{ 2 } } -1-{ k }^{ 2 }\\ \lambda -\frac { 1 }{ 2 } -{ k }^{ 2 }+k\sqrt { 1+{ k }^{ 2 } } =k\sqrt { 1+{ k }^{ 2 } } -1-{ k }^{ 2 }\\ \lambda =\boxed { -\frac { 1 }{ 2 } }

Alternative solution:

Let d d be the direttrice of the parabola and F , A , B , D F', A', B', D' be the projections of the corresponding points onto d d . Then A A = A F = a , B B = B F = b A'A=AF=a,B'B=BF=b and A O = α , B O = β AO=\alpha ,BO=\beta . Since A A A'A and B B B'B are perpendicular to d d , they are parallel to x-axis. That means A F A F = B F B F \frac { AF }{ A'F' } =\frac { BF }{ B'F' } and a α = b β \frac { a }{ \alpha } =\frac { b }{ \beta } .

Since point D D is the symmetry point about the x-axis of point A A : D D = D F = a D'D=DF=a and D F = α D'F'=\alpha . Thus D D D F = a α , B B B F = b β \frac { D'D }{ D'F' } =\frac { a }{ \alpha } ,\frac { B'B }{ B'F' } =\frac { b }{ \beta } . Since D D D F = B B B F \frac { D'D }{ D'F' } =\frac { B'B }{ B'F' } and D D D F , B B B F D'D\bot D'F',B'B\bot B'F' , we have two similar triangles: Δ F D D = Δ F B B \Delta F'D'D=\Delta F'B'B . That means D F D = B F B \angle DF'D'=\angle BF'B' , so points F , B , D F',B,D lay on one line B D BD . That means B D BD intersects with x-axis at point F F' .

Point F F' is a projection of the focus on the direttrice, so F = ( p 2 , 0 ) F'=\left( -\frac { p }{ 2 } ,0 \right) .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...